Cross-sectional study to analyse the pattern of smartphone usage among adolescents in urban slum of a metropolitan city - Qureshi, Kamran; Thore, Pooja; Rajan, Sneha (International Journal Of Community Medicine And Public Health, 2022)
Background: Adolescents are defined as young people between the ages of 10 to 19 years. Smartphone is a term used to distinguish mobile phone with advanced features from basic feature phones. Modern smartphones currently include all the features of a laptop, including web browsing, Wi-Fi and 3rd-party apps etc. Indian teens are currently driving the smartphone market in India. Methods: A cross-sectional study was done in an urban slum of a metropolitan city.100 adolescents aged between 10 to 19 years were assessed using pre-structured questionnaire and prior informed parental consent and assent were taken. The questionnaire included questions about socio-demographic profile and questions pertaining to the use of smartphones in relation to time and frequency and regarding use of internet and games on the phone by the adolescents. Results: Among the 100 participants, mean age was 14.29 years. 93% of the participants were using smartphones, 48.4% were using smartphones since 1 to 3 years and 46.2% used phones between 1 to 3 hours daily. 96.7% used internet on the phone, 72.04% participants have social media accounts and 64.5% played games on phones. The most relevant smartphone function was social networking. Conclusions: Results show increasing dependency of adolescents on smartphones. Although smartphones offer several conveniences in our life, we need to be aware of the negative effects of smartphone use, the most concerning aspect being smartphone addiction.